Environmental Jurisprudence (Fiqh al-Bi’ah): Formulating Islamic Legal Responses to the Contemporary Ecological Crisis through the Lens of Maqasid al Shari’ah - Nur Helmy Iffah Wafiyah (Cv. Kayaswara, 2026)
This article examines the theoretical foundations and practical formulation of fiqh al-bi’ah (Islamic environmental jurisprudence) as a normative legal framework for addressing the contemporary ecological crisis. Employing a qualitative-analytical methodology grounded in uṣūl al-fiqh (Islamic legal theory) and maqāṣid al-sharī’ah (higher objectives of Islamic law), this study interrogates the classical jurisprudential corpus to extract, systematize, and reformulate ecological principles responsive to twenty-first-century environmental degradation. The analysis demonstrates that the Qur’anic concepts of khilāfah (vicegerency), amānah (trust), and mīzān (balance) constitute a coherent eco-theological paradigm from which binding legal norms can be derived. The study proposes an expanded maqāṣid framework that incorporates ḥifẓ al-bi’ah (preservation of the environment) as a sixth essential objective alongside the five classical ḍarūriyyāt. Through critical engagement with both classical sources and contemporary scholarship, the article argues that fiqh al-bi’ah represents not merely an ethical aspiration but a juridically actionable domain capable of generating enforceable rulings on pollution, resource depletion, biodiversity loss, and climate change. The findings contribute to ongoing debates in Islamic legal philosophy regarding the adaptability of sharī’ah to emergent global challenges and offer a framework for Muslim-majority states to integrate ecological imperatives into positive law.